Synthesis, Characterization, Spectral and Antimicrobial Studies on Some Mixed Complexes of Transition Metal - PABREJ, D.S.; PATEL, K.P.; Parikh, S.C. (Asian Journal of Chemistry, 2010)
Some new ternary complexes of Mn(II) and Ni(II) with 8-hydroxy quinoline as primary and glycine, lysine, alanine as secondary ligands have been synthesized and their structural features have been studied on the basis of analytical and spectral data. Analytical data suggest 1:1:1 stoichiometric composition for the isolated ternary complexes. IR spectra confirm the primary and secondary ligands are co-ordinated through O/N donor atoms. Antimicrobial activity of the complexes have also been studied.